Observasi Metode Pembelajaran PPKN Di SMP Negeri 35 Medan - Joy Novi Yanti Lumbantobing; Jojor Mindo Manullang; Murniwati Lase; Al Firman; Reylan Silverius Sinaga (International Forum of Researchers and Lecturers, 2023)
This article is entitled